1995
DOI: 10.1111/j.1432-1033.1995.0316n.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-peptide Sera Against Cell-CAM 105 Determine High Molecular-mass Variants of the Long Isoform in Rat Hepatocytes

Abstract: The glycoprotein cell‐CAM 105 is a member of the carcinoembryonic‐antigen‐(CEA)‐gene family, involved in cell‐cell adhesion of rat hepatocytes and expressed on the cell surface as a long (L) and a short (S) isoform with slightly differing molecular masses and isoelectric points. The cDNA of the L‐isoform has been isolated and sequenced, as confirmed by the preparation of specific anti‐peptide sera [Lin, S.‐H., Culic, O., Flanagan, D. & Hixson, D. C. (1991) Biochem. J. 278, 155–161]. Recently, two additional cD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…Mouse anti-human HLA antibody was purchased from Sigma-Aldrich (Sigma-Aldrich Co., St. Louis, MO). The preparation of polyclonal rabbit antipeptide antibodies specific for the CEACAM1-4L and CEA-CAM1-4S has been previously described [36]. The secondary antibodies used for indirect immunofluorescence labeling were Alexa-488 conjugated goat anti-mouse and goat anti-mouse-HRP conjugated secondary antibody (Invitrogen, Carlsbad, CA, USA).…”
Section: Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mouse anti-human HLA antibody was purchased from Sigma-Aldrich (Sigma-Aldrich Co., St. Louis, MO). The preparation of polyclonal rabbit antipeptide antibodies specific for the CEACAM1-4L and CEA-CAM1-4S has been previously described [36]. The secondary antibodies used for indirect immunofluorescence labeling were Alexa-488 conjugated goat anti-mouse and goat anti-mouse-HRP conjugated secondary antibody (Invitrogen, Carlsbad, CA, USA).…”
Section: Antibodiesmentioning
confidence: 99%
“…Previous reports have demonstrated that dimerization via transmembrane domain helix-helix interactions are often mediated by GXXXG or GXXXA motifs within the transmembrane domain [30,42]. To determine if the GXXXG motifs within the transmembrane domain of CEACAM1-4S played a role in the dimerization of CEACAM1-4S [36,43], the effect of G to L mutations on CEACAM1-4S interactions was analyzed by Blue-Native polyacrylamide gel electrophoresis (BN-PAGE). In BN-PAGE, Coomassie G-250 is used in place of SDS to coat proteins with a uniform negative charge without causing denaturation or disruption of protein-protein interactions [44].…”
Section: Disruption Of Gxxxg Motifs By Double G To L Mutations Causedmentioning
confidence: 99%
“…Tissue transglutaminase, which can be activated by e.g. growth factor‐induced increase of the intracellular calcium concentration [18], is abundantly expressed in liver [10]and it is of particular interest that it is in this tissue that we [8]and others [9]have identified a number of high molecular weight C‐CAM‐L‐containing species. The abundance of a group of proteins with an apparent M r twice that of monomeric C‐CAM, coupled with our demonstration that C‐CAM is distributed as non‐covalently linked dimers within plasma membranes, led us to propose that a population of C‐CAM‐L dimers [8]may become covalently modified.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently demonstrated that C‐CAM is organised as non‐covalently linked dimers within the membranes of epithelial cells [8]. In addition, the detection of C‐CAM‐L‐containing species with apparent molecular masses twice that of monomeric C‐CAM, in extracts of rat liver plasma membranes [8, 9], led us to propose [8]that a population of C‐CAM‐L dimers may become covalently modified, perhaps by the action of tissue transglutaminase.…”
Section: Introductionmentioning
confidence: 99%
“…Monoclonal anti-CEACAM1-mAb Be 9.2, polyclonal anti-CEA-CAM1 serum and isoform-specific antisera were described previously (Becker et al, 1989(Becker et al, , 1993Baum et al, 1995). Polyclonal Clustering Regulates CEACAM1 Signaling 809…”
Section: Antibodiesmentioning
confidence: 99%